Analysis Of Rice Farmers' Income (Oryza Sativa L.) In Jati Makmur Village, North Binjai District - Ambarita, Dewi Natalia; Hernosa, Siswa Panjang (CV Putra Publisher, 2025)
Indonesia is known as an agrarian country where most of the population depends on agriculture, particularly rice farming, which plays a strategic role as both a primary food source and a major income generator for farmers. One of the rice-producing regions in North Sumatra Province is Binjai City, with Jati Makmur Subdistrict identified as an area with high potential but experiencing a decline in rice production over the past two years. This study aims to analyze the income of rice farmers and assess the feasibility of lowland rice farming in Jati Makmur Subdistrict, Binjai Utara District, Binjai City. The research employed a descriptive quantitative approach. A total of 31 farmers were selected from a population of 310 households using simple random sampling. Primary data were collected through observation, interviews, and documentation, while secondary data were obtained from related institutions. The results showed that the average revenue of rice farmers reached IDR 16,395,000 per hectare per planting season, with a total production cost of IDR 6,801,703, resulting in a net income of IDR 9,593,297. The R/C and B/C ratio analysis indicated values greater than 1, suggesting that rice farming in the study area is financially viable and profitable. However, improving cost efficiency, optimizing input use, and providing agricultural support are essential to ensure sustainable farming practices. In conclusion, despite limitations in land size and technology, rice farming in Jati Makmur remains economically feasible and has the potential for further development with appropriate policy support and technical assistance